MARCAS DA VIOLÊNCIA OBSTÉTRICA: UMA ETNOGRAFIA DE EXPERIÊNCIAS VIVIDAS E NARRADAS - Maiara Ricalde Machado Avanci (2024)
This dissertation aims to understand, through ethnographic paths, how parturients build narratives and reports about their births, in the period from 2022 to 2023. This path was taken from the ethnographic dialogue with women who went through negative experiences in the process of parturition, constituted from a common awareness of these experiences, as deeply embedded in violent actions and representations, and from the subsequent analysis of their reports. Understanding the narrative of women who experienced negative and traumatic experiences at such an important moment in their lives meant diving into the deep and particular universe of each one of them, and getting in touch with collectives of aware women who act from the sharing of these experiences.